Post cataract Pseudomonas stutzeri endophthalmitis: Report of a case and review of literature - Ankit Shah; Deepak Senger; Barun Garg; Samarth Mishra; Sugandha Goel; Kumar Saurabh; Rupak Roy (Indian Journal of Ophthalmology, 2020)
We report a rare case of Pseudomonas stutzeri endophthalmitis in an immunocompetent individual along with the review of the literature. A 39-year-old healthy lady presented with sudden painful loss of vision in her right eye. She was diagnosed with postcataract surgery acute endophthalmitis and underwent vitrectomy, intraocular lens explantation and intravitreal antibiotics. P. stutzeri was isolated from vitreous. Though the infection was controlled, the anatomy of the eye could not be salvaged and the right eye became phthisical. P. stutzeri is a rare cause of endophthalmitis with usually poor outcomes.